2015
DOI: 10.1007/s10068-015-0157-1
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant characteristics of ice cream supplemented with sugarcane (Saccharum officinarum L.) juice

Abstract: Antioxidant characteristics of ice cream supplemented with sugarcane juice were investigated. An original 13% sucrose content in ice cream was supplemented with 20, 40, and 60% sugarcane juice (82, 164, and 246 mL/L, treatments T 1 , T 2 , and T 3 , respectively). The sucrose content of all treatments was 13%. DPPH free radical scavenging activities of control, T 1 , T 2 , and T 3 ice cream samples were 5.64±0.19, 16.39±0.15, 37.66±1.21, and 55.78±0.98%, respectively, with total flavonoid contents of 0.18±0.02… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The trend of concentration of phenolic compounds in olein fraction of chia oil is described in literature, Ullah et al. (2015) compared the concentration of phenolic compounds in chia oil and olein fraction of chia oil by HPLC, and olein fraction had considerably higher concentration of chlorogenic and caffeic acids, quercetin, and phenolic glycosides than parent chia oil. Fractionation of palm oil led to increase the concentration of phenolic compounds in low melting point fractions (Kumar & Krishna, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The trend of concentration of phenolic compounds in olein fraction of chia oil is described in literature, Ullah et al. (2015) compared the concentration of phenolic compounds in chia oil and olein fraction of chia oil by HPLC, and olein fraction had considerably higher concentration of chlorogenic and caffeic acids, quercetin, and phenolic glycosides than parent chia oil. Fractionation of palm oil led to increase the concentration of phenolic compounds in low melting point fractions (Kumar & Krishna, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Concentration of bioactive compounds and Ω‐3 fatty acids may be increased by fractionation (Ullah et al., 2017). Amount of unsaturated fatty acids in fats can be considerably increased in olein fractions (Ullah et al., 2015, 2016). Different fractions of palm oil such as palm olein, super olein, palm mid fractions, and palm stearin are commercially produced to cater the needs of food industries.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, little data are presently accessible concerning the flavonoid composition of dairy products enhanced with sugarcane juice [68]. Ullah et al [69] found that, when using sugar cane juice in making ice cream, the total flavonoid contents increased from 0.18 mg QE mL −1 in control samples to 0.51, 0.92, and 1.65 mg QE mL −1 in T1, T2, and T3 mg QE mL −1 in ice cream samples, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Total antioxidative status increased in all experimental groups; however, the highest peak was recorded in fish oil+Szafir linseed and Szafir linseed group [160] Impact of Lactobacillus delbrueckii subsp. bulgaricus, Lactobacillus rhamnosus, Streptococcus thermophilus or Lactobacillus delbrueckii and Lactobacillus fermentum on antioxidant capacity of bovine milk and whey Bacterial strains improved the DPPH free radical scavenging activity, inhibition of superoxide anions and lipid oxidation and reduces the atherogenesis in humans [161] Effect of supplementation of Pirotski Kachkaval by ethanolic extract of Kitaibelia vitifolia on antioxidant characteristics was investigated Supplementation of Pirotski Kachkaval cheese by the ethanolic extract of Kitaibelia vitifolia raised the antioxidant capacity of cheese [162] Antioxidant characteristics of ice cream were increased by partially replacing the sucrose with sugarcane juice Addition of sugarcane juice in ice cream increased the total phenolic contents, DPPH free radical scavenging activity, nitric oxide free radical scavenging activity, and total antioxidant capacity of ice cream [163] Interesterified blends of butter oil and Moringa oleifera oil were characterized for antioxidant capacity and storage stability Phenolic compounds of Moringa oleifera oil enhanced the antioxidant perspectives and storage stability of butter oil in long-term storage [164] Peel extract was determined on antioxidant characteristics of whey butter Addition of 400 ppm ethanolic extract of almond peel increased the total phenolic contents and DPPH free radical scavenging activity [25] Cheddar cheese was supplemented with mango (Mangifera indica L.) oil to improve the antioxidant characteristics Supplementation of mango kernel oil increased the total phenolic contents, DPPH free radical scavenging activity, and nitric oxide free radical scavenging activity and inhibited the lipid oxidation [165] Influence of interesterified Moringa oleifera oil on oxidative stability of ice cream was studied Addition of interesterified Moringa oleifera oil significantly improved the oxidative stability of ice cream [165] The main objective of this study was to raise the antioxidant characteristics of cheddar cheese of chia oil. Cheddar was supplemented with chia (Salvia hispanica L.) oil from 2.5% to 10% Supplementation of cheddar cheese with chia oil increased the antioxidant capacity of cheddar cheese [166] Table-6: Antioxidant characteristics of some dairy products.…”
Section: Lactobacillus Delbrueckiimentioning
confidence: 99%